If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 11 = -101 + -10x Reorder the terms: 11 + 6x = -101 + -10x Solving 11 + 6x = -101 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 11 + 6x + 10x = -101 + -10x + 10x Combine like terms: 6x + 10x = 16x 11 + 16x = -101 + -10x + 10x Combine like terms: -10x + 10x = 0 11 + 16x = -101 + 0 11 + 16x = -101 Add '-11' to each side of the equation. 11 + -11 + 16x = -101 + -11 Combine like terms: 11 + -11 = 0 0 + 16x = -101 + -11 16x = -101 + -11 Combine like terms: -101 + -11 = -112 16x = -112 Divide each side by '16'. x = -7 Simplifying x = -7
| 2x+20=12x-70 | | 3(2x-1)+7=4 | | 10x-10=110 | | 4(2-x)=7(2x-4) | | 3x+36=13x-74 | | Y=12x | | 4+3(2x+4)-4=-42 | | -8(2+7n)=-6+34 | | 17-4x=5-6x | | 15+b=5b+1+3b | | 3y+16=8y-9 | | 7x+25=10x+16 | | 6x+10=4x+12 | | 5(y-15)=0 | | 28x^7+16x^3-12x^4+20= | | 250+350=x-10+x | | 5a-3a=-36 | | k+20=9k^2 | | -k+20=9k | | 123+(-43)+0+(-15)=123+(-43)+(-15) | | e+(2e+2)=971 | | 2(x+3)=x+9 | | 5x-2=63 | | y=-2x+13 | | 9x-2=70 | | 5x-5=70 | | 5m+6+3(m+2)= | | .333x-.5=.833x | | 8x+6=22 | | 3x-19=-13 | | 4f-7x=11 | | 2=5x+17 |